IMPLEMENTASI PERATURAN DAERAH NO 14 TAHUN 2011 TENTANG RENCANA TATA RUANG DAN WILAYAH KOTA SEMARANG DI KECAMATAN TEMBALANG - Akhmad, Raga Syaikhu; Lituhayu, Dyah; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Flooding in the City of Semarang derived from two sources that is from the sea and from the top of semarang. Regional Semarang over are prioritized for this flood catchment area is established building houses, simple and elite houses. One of the effort from the City Government Semarang by the application of Local Regulation no. 14 years 2011 about spatial plans and the areas of the City of Semarang. This research was conducted in DKTP Semarang as officer of Semarang’s Government. Section of Regional planing and supervision as stakeholder of the Implementation Of The Local Regulation No 14 2011. This Research is based on the rise of the construction of housing in the area of the City of Semarang over especially in Kecamatan Tembalang is not in reflect with RTRW of Semarang City. The purpose of this research is described and analyze Implementation Of Regulation No 14 2011 and analyze what factors which influence the Implementation Of Regulation No 14 2011 the City of Semarang. The results of the study showed that in its implementation there are a number of things can restrickting the implementation of this local regulations. This is due to a lack of human resources , obscurity standards and target of this policy and the less participation of the community and private sectors caused by social and economic conditions. Recommendations from this research are to recruit of human resources to handling the problem , the implementation of RDRTK as a continuity of Semarang’s RTRW , and listen to public aspiration.